Trade, technology and skills: Evidence from Turkish microdata - Elena Meschi; Erol Taymaz; Marco Vivarelli (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2009)
In this paper we report evidence on the relationship between trade openness, technology adoption and the relative demand for skilled labour in the Turkish manufacturing sector, using firm level data over the period 1980-2001. In a dynamic panel data setting, using a unique database comprising data from 17,462 firms, we estimate an augmented cost share equation whereby the wage bill share of skilled workers in a given firm is related to international exposure and technology adoption. Both at the sectoral and firm level, it emerged that R&D expenditures are positive and significantly related to skill upgrading. This result supports the skill biased technological change argument in the case of a middle-income country such as Turkey. Moreover, the sectoral analysis revealed that increasing export towards more industrialised countries (mainly the E.U.) tends to shift the production toward less skill-intensive activities. While this result is consistent with the HOSS theorem, on the other hand import penetration from more developed countries turns out to facilitate the adoption of new technologies embodied in capital and intermediate goods, thus shifting the production toward more skill-intensive technologies. This result is confirmed by the firm level analysis that finds a positive impact of technological transfer from abroad, foreign ownership and export on the demand for skills, highlighting the role of increasing globalisation in fostering skill upgrading within firms. Our microdata also allowed us to investigate the direct impact of import flows in shaping the relative demand for skills. The results showed that those firms belonging to the sectors that most raised their inputs from more developed countries also experienced a higher increase in their labour cost share of skilled workers. This finding is a further support to the hypothesis that imports from industrialised countries imply a transfer of new technologies, in turn leading to a higher demand for skilled labour.
Keywords: F16; O15; O33; 330; globalization; technology transfer; skills; panel data; GMM-SYS; Verarbeitendes Gewerbe; Arbeitsnachfrage; Hochqualifizierte Arbeitskräfte; Außenhandelsliberalisierung; Technologietransfer; Globalisierung; Technischer Fortschritt; Qualifikation; Türkei